Urinary incontinence and the criteria of frailness among the elderly outpatients - Silva, Vanessa Abreu da; Souza, Katia Lacerda de; D’Elboux, Maria José (Revista da Escola de Enfermagem da USP, 2011)
The objectives of this study were to verify the occurrence of urinary incontinence (UI) and its characteristics in pre-frail and frail elderly patients of a geriatrics outpatient clinic, compare the presence of frailness criteria among the elderly with and without UI and identify among the frailty criteria the chance of risk for UI among those elderly outpatients. Participants were 100 elderly individuals, with an average age of 76.2 years; 65 participants reported UI, 71.3% of which presented three or more frailness criteria. The occurrence of UI was greater in frail participants (p=0.0011). Multivariate analysis showed that the criteria slowness (OR=4.99) and exhaustion (OR=4.85) has a statistically significant relation with UI. The occurrence of UI was high and participants who presented slowness have a risk almost five times greater to presenting UI while those reporting exhaustion have a risk five times greater for UI compared to those without these criteria.